Existence and nonlinear stability of stationary solutions to the full two-phase flow model in a half line. (June 2021) - Li, Hai-Liang; Zhao, Shuang
Abstract: The inflow problem for the full two-phase model in a half line is investigated in this paper. The existence and uniqueness of the stationary solution are shown and its nonlinear stability of the stationary solution is established for the small perturbation.